The Effect of Financial Leverage, Company Sizes, Basic Earning Power and Activity Ratio to Earning Per Share - Berlian Karlina; Muhamad Rifki Ramadhan (International Journal of Business Studies, 2020)
The purpose of this research is showed to know the effect of Financial Leverage, Firm Size, Basic Earning Power and Activity Ratio to Earning Per Share on manufactured companies automotive and components sub-sector that listed on Indonesian Stock Exchange period 2013-2017. Sampling is done by purposive sampling method. The population in this research were 13 companies and the sample used were 12 manufacturing companies of automotive and components sub sector that listed on Indonesian Stock Exchange period 2013-2017. The method used in this research is hypothesis testing method. The analytical tool used is multiple linear regression analysis tested by using Program SPSS version 20 and Microsoft Excel 2016. The data used is secondary data in the form of complete financial statements during research period. The result of this research shows that Financial Leverage, Firm Size and Basic Earning Power have an effect to Earning Per Share. While Activity Ratio has no effect to Earning Per Share.